Vloga časopisov pri vzpostavljanju nacionalizmov - Amon Prodnik, Jernej (Teorija in praksa, 2018)
The newspaper Slovenski narod (Slovenian Nation) was initially published in 1868 and became the first daily paper to be published in the Slovenian language in 1873. Like most other newspapers published in the 19th century, it was firmly entrenched in political struggles. The paper focuses on its role in imagining and expanding the Slovenian national identity. The study is based on the process of how communities become imagined through the construction of specific solidarities (Benedict Anderson), while also focusing on the direct promotion of national identity via nationalistic content in newspapers. Slovenski narod is analysed in the context of the rise of nationalisms that characterised the 19th century, with newspapers published in the Slovenian language related to periodicals released in other comparable states and milieus. I was interested in whether similar tendencies existed elsewhere - thus enabling a wider, international perspective - and whether any generalisations are possible. Because the 19th century was defined by deep social transformations that went beyond local frameworks, the analysed institutions and processes are dealt with in the context of the long 19th century.
Keywords: History of journalism; Nacionalizem; Nationalism; Political press; Politični tisk; Slovenian newspapers; Slovenski časniki; Slovenski narod (periodična publikacija); Zgodovina novinarstva